Innovative Homestays and Eco-Friendly Accommodation as Tourist Attractions - Desma Erica Maryati Manik; Hommy Dorthy Ellyany Sinaga; Yulvitriyani Br Sebayang; Muhammad Hafiz Abd.Rashid; Marwan Marwan; Sipnarong Kanchawongpaisan (Eastasouth Journal of Effective Community Services, 2025)
Rural areas with natural potential and agrarian atmosphere such as Pematang Johar Village present opportunities to be developed into sustainable tourism destinations. However, limitations in lodging facilities and lack of environmentally friendly practices become obstacles in optimizing that potential. Therefore, this community-service activity aims to design and assist the implementation of eco-friendly homestays and lodgings as a new tourist attraction in the village. The implementation methods consist of initial observation and problem identification, training and assistance for lodging managers/owners and community members, and post-implementation evaluation. The results show increased environmental awareness among homestay managers and the community, evidenced by improved building design using local/natural materials, implementation of waste management systems and greening the environment, and establishment of environmentally friendly homestay service standards. These findings indicate that eco-friendly homestay development can serve as an alternative lodging option that strengthens the village’s tourism appeal while supporting environmental preservation and community empowerment. Thus, environmentally conscious lodging innovation is worthy to be adopted as a sustainable tourism model in Pematang Johar Village, with a recommendation that management continues participatively and receives support from the village authority for sustainability.